Basic inequality on a b-metric space and its applications - Tomonari Suzuki (Journal of Inequalities and Applications, 2017)
Abstract We first prove one of the most basic inequalities on a b-metric space. And then we prove some fixed point theorems. We also consider two similar conditions; one implies the Cauchyness on sequences but the other does not.